PERASAAN KESEPIAN DAN SELF-ESTEEM PADA MAHASISWA - Yurni Yurni (Universitas Batanghari Jambi, 2015)
Background : Loneliness become one of vital issues in college student, at any degrees anyone of them have felt of loneliness. Male or female student are both have the opportunity to feel alone depend on their own situation and condition. Self-esteem is become another problem faced by a college student. Low self esteem may impact students live such as lack of self-worth, lack of self-confidence and having no goal pursuit behavior. The objective of this research was to find the relationship between gender, loneliness and self esteem among college student at teacher training Faculty, Batanghari University Jambi.Method: about 76 college student at teacher training faculty, Batanghari University Jambi 18 male and 56 female was taken as subject of the research by using incidental random sampling technique. Self esteem scale from Sorensen was delivered to the subject, mean while for loneliness it was used 20 question of loneliness scale from schmit and sermat (1983). It reveal four category of loneliness, friendship, family, romantic relationship and group.Result: Data gained by using pearson correlation showed there were significant correlation between gender, loneliness and self-esteem. t-count 0.549and t-table 0.227 its mean that hypotheses stated that there were correlation between gender to loneliness and self-esteem was accepted. Majority of subject have loneliness in friendship. Subject have low to severe self-esteem, gender didn’t make the difference. Key words : loneliness, self esteem